Uniformly dispersed primary impression silicone rubber and preparation method thereof

By controlling the density and particle size combination of inorganic fillers and employing stepwise low-temperature kneading and vacuum treatment, the problem of uneven dispersion of primary molding silicone rubber was solved, achieving efficient and precise molding preparation and improving the mechanical properties and operational stability of the material.

CN121045844APending Publication Date: 2025-12-02LIAONING UPCERA CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511370407.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-24
Publication Date
2025-12-02

AI Technical Summary

Technical Problem

In the preparation of primary impression silicone rubber, the high proportion of inorganic fillers in the existing technology leads to long mixing time, high energy consumption, and uneven dispersion, which affects the structural uniformity and performance stability of the material, resulting in decreased impression accuracy and fluctuations in operation time.

Method used

By controlling the combination of loose density, tap density and particle size of inorganic filler silica powder and fumed silica, and by using stepwise low-temperature kneading and vacuum treatment, the filler is ensured to be uniformly dispersed in silicone rubber, reducing stirring resistance and improving processing efficiency.

Benefits of technology

It achieves high-precision and high-efficiency preparation of primary impression silicone rubber, with low surface roughness, high impression accuracy, significantly improved tensile strength and tear strength, and shortened operation time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121045844A_ABST
    Figure CN121045844A_ABST
Patent Text Reader

Abstract

The invention discloses uniformly-dispersed primary impression silicone rubber and a preparation method thereof, and relates to the technical field of silicone rubber, physical parameters such as apparent density, tap density, compression ratio and the like of inorganic filler silica powder and fumed silica are regulated and controlled, so that the inorganic filler silica powder and the fumed silica are mutually coordinated and matched in a specific range; therefore, highly uniform dispersion of the filler in the silicone rubber matrix is realized. According to the method, the processing property of the material is remarkably improved, and the processing time required by operation is effectively shortened. The prepared silicone rubber impression is fine in surface, the roughness is remarkably reduced, and excellent surface quality is shown. Meanwhile, the dimensional stability and the shape fidelity are greatly improved, extremely high impression precision and copy authenticity are ensured, and the fine structure of the oral cavity tissue can be accurately reproduced. The product has excellent comprehensive performance and is suitable for the field of oral cavity primary impression with high precision requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of silicone rubber technology, and more specifically, to a uniformly dispersed primary impression silicone rubber and its preparation method. Background Technology

[0002] In dental prosthetics, the accuracy and stability of impression materials directly determine the fit of the final restoration. Silicone rubber impression materials, due to their excellent detail reproduction capabilities, good elastic recovery rate, and stable chemical properties, have become an irreplaceable key material in clinical applications. The primary impression silicone rubber is typically a heavy body of condensation-type or addition-type silicone rubber, requiring high mechanical strength to ensure it is not easily deformed or torn when removed from the oral cavity and to withstand the external pressure during the molding process. To achieve this performance requirement, a large amount of inorganic filler is usually added to the base polymer during the manufacturing process, with the filler ratio reaching 40% to 60% or even higher.

[0003] However, the traditional mixing process of "one-time feeding and mechanical stirring" that is currently widely used has significant drawbacks when faced with such a high proportion of fillers and a high-viscosity system: First, the rapid increase in material viscosity leads to high stirring resistance, long mixing time, and high energy consumption, placing stringent requirements on equipment power and structure, resulting in low production efficiency; Second, fillers are difficult to disperse uniformly in a high-viscosity environment, and problems such as agglomeration, local enrichment, or bubble encapsulation are prone to occur, affecting the structural uniformity of the material; Third, the final performance of the material is affected, manifested as decreased impression accuracy, insufficient dimensional stability, inconsistent mechanical properties, and fluctuations in operation time, which seriously affect the reliability and repair effect of clinical use.

[0004] In view of this, the present invention is proposed. Summary of the Invention

[0005] The purpose of this invention is to provide a uniformly dispersed primary molding silicone rubber and its preparation method. By controlling the loose density, tap density, and compression ratio of the inorganic filler silica powder and fumed silica to be coordinated within a certain range, the processing time for preparing the primary molding silicone rubber is significantly shortened, the surface roughness of the primary molding silicone rubber is small, and the molding accuracy is high.

[0006] This invention is implemented as follows: In a first aspect, the present invention provides a uniformly dispersed primary molding silicone rubber, wherein the primary molding silicone rubber comprises, by weight percentage: 30-80 wt% vinyl polydimethylsiloxane, 11-80 wt% inorganic filler, 1-20 wt% hydrogen-containing crosslinking agent, 0-0.5 wt% inhibitor, and 0.01-5 wt% catalyst; The inorganic filler includes silica powder and fumed silica powder, wherein the loose packing density of the silica powder is 0.3-1 g / cm³. 3Tap density: 0.9-1.8 g / cm³ 3 The compression ratio is 1.5-2.6; the loose packing density of the fumed silica is 0.02-0.2 g / cm³. 3 Tap density: 0.05-0.23 g / cm³ 3 The compression ratio is 1.4-2.2.

[0007] In an optional embodiment, the median particle size D50 of the silicon micropowder is 4-20 μm and the content is 10-50 wt%; the median particle size D50 of the fumed silica powder is 1-100 nm and the content is 1-30 wt%.

[0008] In an optional embodiment, the median particle size D50 of the silicon micropowder is 5-15 μm; the median particle size D50 of the fumed silica powder is 1-30 nm.

[0009] In an optional embodiment, the initial impression silicone rubber comprises the following components by weight percentage: 40-70 wt% vinyl polydimethylsiloxane, 20-40 wt% silica powder, 5-20 wt% fumed silica powder, 3-15 wt% hydrogen-containing crosslinking agent, 0-0.5 wt% inhibitor, and 0.02-2 wt% catalyst.

[0010] In an optional embodiment, the viscosity of the vinyl polydimethylsiloxane is in the range of 10,000-100,000 mPa·s; the Si-H content in the hydrogen-containing crosslinking agent is 0.3-2.2 wt%; the inhibitor is at least one of alkynyl alcohols or maleate esters; and the catalyst is a platinum catalyst, wherein the Pt content in the platinum catalyst is 1,000-20,000 ppm.

[0011] In an optional embodiment, the viscosity of the vinyl polydimethylsiloxane is 30,000-80,000 mPa·s; and the Pt content in the platinum catalyst is 10,000-20,000 ppm.

[0012] Secondly, the present invention provides a method for preparing uniformly dispersed primary impression silicone rubber, comprising the following steps: vacuum drying of silica micro powder and fumed silica to obtain dried powder; adding the dried powder to vinyl polydimethylsiloxane for a first kneading; then performing a second kneading after vacuum treatment; cooling after kneading, and then sequentially adding a crosslinking agent, a catalyst, and an inhibitor, followed by vacuum degassing to obtain primary impression silicone rubber.

[0013] In an optional embodiment, the vacuum drying temperature is 110℃-130℃, the vacuum degree is -0.06 to -0.08 MPa, and the drying time is 20-30 min.

[0014] In an optional embodiment, the first kneading is performed at a rotation speed of 1-30 rpm, a temperature of 10℃-30℃, and a kneading time of 10-20 min; the second kneading is performed at a vacuum degree of -0.09 to -0.1 MPa, a rotation speed of 1-30 rpm, and a kneading time of 10-20 min.

[0015] In an optional embodiment, the cooling temperature is ≤25℃; the vacuum degree of the vacuum degassing is -0.09 to -0.1 MPa, the temperature is 10℃ to 30℃, and the time is 10 to 15 min.

[0016] The present invention has the following beneficial effects: This invention uses inorganic fillers with different loose density, tap density, and compression ratio in combination. Within a certain range, these filler particles are coordinated to achieve a tight arrangement, reducing internal porosity and reducing stirring resistance during processing, thus significantly improving processing efficiency, enhancing powder dispersion, and ensuring good processing at room temperature. The processing time for preparing primary molding silicone rubber is significantly shortened, and the surface roughness of the primary molding silicone rubber is small, resulting in high molding accuracy. Attached Figure Description

[0017] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0018] Figure 1 This is a SEM image of the powder without agglomeration in the embodiments of this application; Figure 2 This is a SEM image of a very small amount of powder agglomeration in an embodiment of this application; Figure 3 This is a SEM image of the micro-agglomeration of powder in the embodiments of this application; Figure 4 This is a SEM image of a small amount of powder agglomeration in an embodiment of this application. Detailed Implementation

[0019] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0020] The following is a detailed description of a uniformly dispersed primary molding silicone rubber and its preparation method provided by the present invention.

[0021] In a first aspect, the present invention provides a uniformly dispersed primary molding silicone rubber, wherein the primary molding silicone rubber comprises the following components by weight percentage: 30-80 wt% vinyl polydimethylsiloxane, 11-80 wt% inorganic filler, 1-20 wt% hydrogen-containing crosslinking agent, 0-0.5 wt% inhibitor, and 0.01-5 wt% catalyst, wherein the sum of the weight percentages of each component is 100%; The inorganic filler includes silica powder and fumed silica powder, wherein the loose packing density of the silica powder is 0.3-1 g / cm³. 3 Tap density: 0.9-1.8 g / cm³ 3 The compression ratio is 1.5-2.6; the loose packing density of the fumed silica is 0.02-0.2 g / cm³. 3 Tap density: 0.05-0.23 g / cm³ 3 The compression ratio is 1.4-2.2.

[0022] The formula for calculating the compression ratio is as follows:

[0023] Loose packing density indicates the initial state of the powder, while tapped density expresses the volume change brought about by the processing. Compression ratio reflects the powder's flowability during processing; powders with specific compression ratios exhibit different flowabilities. Generally, fumed silica has very low loose packing and tapped densities, while silica micropowder has relatively high loose packing and tapped densities. Appropriate proportions allow for a more rational arrangement of their volumetric space. Powders with lower density have greater buoyancy and are difficult to mix, while powders with higher density forcibly incorporate them into the matrix and disperse them between particles. The inventors mixed fumed silica and silica micropowder in a specific ratio, achieving a synergistic effect through density difference. The high-density silica micropowder acts as a framework, providing space and effectively encapsulating the extremely light and easily floating fumed silica during processing, forcing its dispersion. The fumed silica fills the voids between silica micropowder particles. The combination of the two significantly improves mixing uniformity and filling density, reduces porosity, and ultimately enhances the compactness and mechanical properties of the composite material.

[0024] In some optional embodiments, the median particle size D50 of the silicon micropowder is 4-20 μm, preferably 5-15 μm, such as 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm or 20 μm, etc., or other values ​​within the range of 4-20 μm; the content of the silicon micropowder is 10-50 wt%, preferably 20-40 wt%, such as 10 wt%, 20 wt%, 30 wt%, 40 wt% or 50 wt%, etc., or other values ​​within the range of 10-50 wt%.

[0025] In some optional embodiments, the median particle size D50 of the fumed silica powder is 1-100 nm, preferably 1-30 nm, such as 1 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm, etc., or other values ​​in the range of 1-100 μm; the content of the fumed silica powder is 1-30 wt%, preferably 5-20 wt%, such as 1 wt%, 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt% or 30 wt%, etc., or other values ​​in the range of 1-30 wt%.

[0026] It should be noted that the contents of the silicon micro powder and the fumed silica powder are based on the total weight of the initial impression silicone rubber.

[0027] In some alternative embodiments, the primary impression silicone rubber comprises the following components by weight percentage: 40-70 wt% vinyl polydimethylsiloxane, 20-40 wt% silica powder, 5-20 wt% fumed silica powder, 3-15 wt% hydrogen-containing crosslinking agent, 0-0.5 wt% inhibitor, and 0.02-2 wt% catalyst.

[0028] In some alternative embodiments, the viscosity range of the vinyl polydimethylsiloxane is 10,000-100,000 mPa·s, preferably 30,000-80,000 mPa·s, such as 10,000 mPa·s, 20,000 mPa·s, 30,000 mPa·s, 40,000 mPa·s, 50,000 mPa·s, 60,000 mPa·s, 70,000 mPa·s, 80,000 mPa·s, 90,000 mPa·s, or 10,000 mPa·s, or other values ​​in the range of 10,000-100,000 mPa·s.

[0029] It should be noted that the viscosity of the vinyl polydimethylsiloxane is the viscosity at 25°C.

[0030] The viscosity of the aforementioned polydimethylsiloxane gives the material both good flowability and appropriate consistency, making it easy to fully spread and fill in detailed areas of the oral cavity, accurately replicating the morphology of the gingival sulcus and tooth preparation area, and avoiding air bubble formation. At the same time, this viscosity ensures that the silicone rubber maintains a stable shape during the procedure, preventing it from flowing and deforming, thus obtaining a clear and highly accurate impression, providing a reliable foundation for the subsequent fabrication of restorations.

[0031] In some alternative embodiments, the Si-H content in the hydrogen-containing crosslinking agent is 0.3-2.2 wt%. The Si-H in the hydrogen-containing crosslinking agent undergoes a sufficient and moderate crosslinking reaction with vinyl polydimethylsiloxane, allowing the material to cure rapidly after the operating time, forming a structurally stable and highly elastic rubber network. Too low a content will result in insufficient crosslinking, slower curing, and poor impression strength; too high a content may lead to an excessively rapid reaction, shortening the operating time and easily causing stress cracking. This range perfectly balances operability and curing reliability, which is key to obtaining high-precision, non-deformation impressions.

[0032] In some alternative embodiments, the inhibitor is at least one of alkynyl alcohols or maleate esters; the alkynyl alcohols include, but are not limited to, methylbutynyl alcohol, etynylcyclohexanol, and dimethylhexynyl alcohol; the maleate esters include, but are not limited to, diallyl maleate and diethyl fumarate.

[0033] The aforementioned inhibitors can precisely control the progress of the hydrosilylation reaction by forming reversible coordination with the platinum catalyst. This effectively delays curing at room temperature, providing sufficient and stable working time to ensure that the impression material is fully cast and captures details in the oral cavity. Simultaneously, the inhibitory effect is rapidly relieved at body temperature, achieving rapid and thorough curing, ultimately resulting in a silicone rubber impression with precise morphology and no internal defects. This characteristic perfectly balances clinical operability and curing reliability.

[0034] In some alternative embodiments, the catalyst is a platinum catalyst, including but not limited to isopropanol chloroplatinate solution, vinylplatinum complex, and platinum-divinyltetramethyldisiloxane complex (Karstedt catalyst). The Pt content in the platinum catalyst is 1000-20000 ppm, preferably 10000-20000 ppm, such as 1000 ppm, 5000 ppm, 10000 ppm, 15000 ppm, or 20000 ppm, or other values ​​in the range of 1000-20000 ppm.

[0035] The catalysts described above can provide sufficiently high catalytic activity to ensure that the materials are rapidly and fully cross-linked and cured at oral cavity temperatures, forming a dense and mechanically stable impression; while avoiding excessive platinum content that could lead to excessively fast reactions, insufficient operating time, or unnecessary increases in costs.

[0036] Secondly, the present invention provides a method for preparing uniformly dispersed primary impression silicone rubber, comprising the following steps: S1. Silicon micro powder and fumed silica are vacuum dried to obtain dried powder.

[0037] In some alternative embodiments, the vacuum drying temperature is 110℃-130℃, the vacuum degree is -0.06 to -0.08 MPa, and the drying time is 20-30 min.

[0038] S2. Add dry powder to vinyl polydimethylsiloxane for the first kneading, then perform vacuum treatment and a second kneading.

[0039] In some alternative embodiments, the first kneading is performed at a speed of 1-30 rpm, a temperature of 10℃-30℃, and a kneading time of 10-20 min; the second kneading is performed at a vacuum of -0.09 to -0.1 MPa, a speed of 1-30 rpm, and a kneading time of 10-20 min.

[0040] S3. After kneading, cool the mixture, then add the crosslinking agent, catalyst, and inhibitor in sequence, followed by vacuum degassing to obtain the initial impression silicone rubber.

[0041] In some alternative embodiments, the cooling temperature is ≤25°C; the vacuum degree of the vacuum degassing is -0.09 to -0.1 MPa, the temperature is 10°C to 30°C, and the time is 10 to 15 minutes.

[0042] The preparation method provided by this invention effectively solves the core problems of powder agglomeration and uneven dispersion in impression materials through stepwise low-temperature kneading and precise vacuum control, and also effectively shortens the processing time. First, the powder is preheated and vacuum dried to thoroughly remove moisture and prevent air bubbles in subsequent operations. Then, it is initially mixed with vinyl silicone oil under low-speed shearing to avoid introducing too much air and localized overheating during high-speed stirring. Next, it undergoes deep kneading under high vacuum to fully wet and disperse the powder, eliminating entrained gas. Finally, the active component is added and degassing is performed to ensure that the final product has a uniform texture and is free of air bubbles, thereby obtaining a dental impression silicone rubber that is smooth to handle, dimensionally stable, and has extremely high precision.

[0043] The method for preparing the initial impression silicone rubber proposed in this invention has a processing time of ≤2h from feeding to discharge, a roughness of <0.3mm, an impression accuracy of ≤50μm, a tensile strength of ≥4MPa, a tear strength of ≥11N / mm, and a Shore A hardness of 50-70.

[0044] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0045] Example 1 This embodiment provides a primary molding silicone rubber, which, by weight percentage, comprises the following raw materials: 70wt% vinyl polydimethylsiloxane, 20wt% silica powder, 5wt% fumed silica, 15wt% hydrogen-containing crosslinking agent, 0.02wt% 3-methyl-1-butyn-3-ol and 0.02wt% platinum catalyst.

[0046] The viscosity of vinyl polydimethylsiloxane is 30000 mPa·s; the median particle size D50 of the silica powder is 4 μm, and the bulk density is 0.35 g / cm³. 3 Tap density 0.9 g / cm³ 3 The compression ratio is 2.57; the median particle size D50 of the fumed silica is 1 nm, and the loose packing density is 0.02 g / cm³. 3 Tap density 0.05 g / cm³ 3 The compression ratio is 2.5; the Si-H content of the hydrogen-containing crosslinking agent is 0.3wt%; and the Pt content in the platinum catalyst is 10000ppm.

[0047] Its preparation method includes the following steps: S1. Place the silica powder and fumed silica in a vacuum oven and dry at 120℃ and -0.08MPa for 30 min. S2. Add vinyl polydimethylsiloxane to the kneader, maintain 10°C, add the dry powder in 3 batches with an interval of 2 minutes between each batch, knead at a speed of 5 rpm, for a total time of 20 minutes; evacuate to -0.09 MPa and continue kneading for 15 minutes. S3. Cool to 18°C, add crosslinking agent, catalyst and inhibitor in sequence, degas under vacuum at -0.09MPa for 10 minutes, and flatten the 2mm sheet with a glass plate.

[0048] Example 2 This embodiment provides a primary molding silicone rubber, which, by weight percentage, comprises the following raw materials: 60wt% vinyl polydimethylsiloxane, 25wt% silica powder, 15wt% fumed silica, 5wt% hydrogen-containing crosslinking agent, 0.05wt% 3-methyl-1-butyn-3-ol and 0.2wt% platinum catalyst.

[0049] The viscosity of vinyl polydimethylsiloxane is 60,000 mPa·s; the median particle size D50 of the silica powder is 6 μm, and the bulk density is 0.7 g / cm³. 3 Tap density 1.3 g / cm³ 3 The compression ratio is 1.86; the median particle size D50 of fumed silica is 12 nm, and the loose packing density is 0.01 g / cm³. 3 Tap density 0.14 g / cm³ 3 The compression ratio is 1.4; the Si-H content of the hydrogen-containing crosslinking agent is 0.8 wt%; and the Pt content in the platinum catalyst is 15000 ppm.

[0050] Its preparation method includes the following steps: S1. Place the silica powder and fumed silica in a vacuum oven and dry at 120℃ and -0.08MPa for 30 min. S2. Add vinyl polydimethylsiloxane to the kneader, maintain 20°C, add the dry powder in 3 batches with an interval of 2 minutes between each batch, knead at a speed of 15 rpm, for a total time of 10 minutes; evacuate to -0.09 MPa and continue kneading for 15 minutes. S3. Cool to 18°C, add crosslinking agent, catalyst and inhibitor in sequence, degas under vacuum at -0.09MPa for 10 minutes, and flatten the 2mm sheet with a glass plate.

[0051] Example 3 This embodiment provides a primary molding silicone rubber, which, by weight percentage, comprises the following raw materials: 65wt% vinyl polydimethylsiloxane, 22wt% silica powder, 13wt% fumed silica, 8wt% hydrogen-containing crosslinking agent, 0.03wt% 3-methyl-1-butyn-3-ol and 0.15wt% platinum catalyst.

[0052] The viscosity of vinyl polydimethylsiloxane is 80,000 mPa·s; the median particle size D50 of the silica powder is 8 μm, and the bulk density is 0.6 g / cm³. 3 Tap density 1.2 g / cm³ 3 The compression ratio is 2.0; the median particle size D50 of the fumed silica is 20 nm, and the loose packing density is 0.08 g / cm³. 3 Tap density: 0.16 g / cm³ 3 The compression ratio is 2.0; the Si-H content of the hydrogen-containing crosslinking agent is 1.0 wt%; and the Pt content in the platinum catalyst is 20,000 ppm.

[0053] Its preparation method includes the following steps: S1. Place the silica powder and fumed silica in a vacuum oven and dry at 120℃ and -0.08MPa for 30 min. S2. Add vinyl polydimethylsiloxane to the kneader, maintain 20°C, add the dry powder in 3 batches with an interval of 2 minutes between each batch, knead at a speed of 20 rpm, for a total time of 15 minutes; evacuate to -0.09 MPa and continue kneading for 20 minutes. S3. Cool to 18°C, add crosslinking agent, catalyst and inhibitor in sequence, degas under vacuum at -0.09MPa for 12 minutes, and flatten the 2mm sheet with a glass plate.

[0054] Example 4 This embodiment provides a primary molding silicone rubber, which, by weight percentage, comprises the following raw materials: 50wt% vinyl polydimethylsiloxane, 35wt% silica powder, 15wt% fumed silica, 3wt% hydrogen-containing crosslinking agent, 0.1wt% 3-methyl-1-butyn-3-ol and 1.0wt% platinum catalyst.

[0055] The viscosity of vinyl polydimethylsiloxane is 100,000 mPa·s; the median particle size D50 of the silica powder is 15 μm, and the bulk density is 0.9 g / cm³. 3 Tap density 1.8 g / cm³ 3 The compression ratio is 2.0; the median particle size D50 of the fumed silica is 30 nm, and the loose packing density is 0.15 g / cm³. 3 Tap density 0.23 g / cm³ 3 The compression ratio is 1.53; the Si-H content of the hydrogen-containing crosslinking agent is 2.2 wt%; and the Pt content in the platinum catalyst is 12000 ppm.

[0056] Its preparation method includes the following steps: S1. Place the silica powder and fumed silica in a vacuum oven and dry at 130℃ and -0.08MPa for 30 min. S2. Add vinyl polydimethylsiloxane to the kneader, maintain 30°C, add the dry powder in 3 batches with an interval of 2 minutes between each batch, knead at a speed of 10 rpm, for a total time of 20 minutes; evacuate to -0.09 MPa and continue kneading for 20 minutes. S3. Cool to 18°C, add crosslinking agent, catalyst and inhibitor in sequence, degas under vacuum at -0.09MPa for 15 minutes, and flatten the 2mm sheet with a glass plate.

[0057] Example 5 This embodiment provides a primary molding silicone rubber, which, by weight percentage, comprises the following raw materials: 55wt% vinyl polydimethylsiloxane, 30wt% silica powder, 10wt% fumed silica, 12wt% hydrogen-containing crosslinking agent, 0.08wt% 3-methyl-1-butyn-3-ol and 0.5wt% platinum catalyst.

[0058] The viscosity of vinyl polydimethylsiloxane is 45000 mPa·s; the median particle size D50 of the silica powder is 10 μm, and the bulk density is 0.5 g / cm³. 3 Tap density 1.1 g / cm³ 3 The compression ratio is 2.2; the median particle size D50 of the fumed silica is 25 nm, and the loose packing density is 0.12 g / cm³. 3 Tap density 0.20 g / cm³ 3 The compression ratio is 1.67; the Si-H content of the hydrogen-containing crosslinking agent is 12wt%; and the Pt content in the platinum catalyst is 18000ppm.

[0059] Its preparation method includes the following steps: S1. Place the silica powder and fumed silica in a vacuum oven and dry at 120℃ and -0.08MPa for 30 min. S2. Add vinyl polydimethylsiloxane to the kneader, maintain 15°C, add the dry powder in 3 batches with an interval of 2 minutes between each batch, knead at a speed of 12 rpm, for a total time of 12 minutes; evacuate to -0.09 MPa and continue kneading for 18 minutes. S3. Cool to 18°C, add crosslinking agent, catalyst and inhibitor in sequence, degas under vacuum at -0.09MPa for 11 minutes, and flatten the 2mm sheet with a glass plate.

[0060] Example 6 This embodiment provides a primary molding silicone rubber, which, by weight percentage, comprises the following raw materials: 70 wt% vinyl polydimethylsiloxane, 25 wt% silica powder, 5 wt% fumed silica, 20 wt% hydrogen-containing crosslinking agent, 0.5 wt% 3-methyl-1-butyn-3-ol and 0.1 wt% platinum catalyst.

[0061] The viscosity of vinyl polydimethylsiloxane is 35000 mPa·s; the median particle size D50 of the silica powder is 12 μm, and the bulk density is 0.4 g / cm³. 3 Tap density 0.95 g / cm³ 3 The compression ratio is 2.38; the median particle size D50 of the fumed silica is 10 nm, and the loose packing density is 0.05 g / cm³. 3 Tap density 0.09 g / cm³ 3 The compression ratio is 1.8; the Si-H content of the hydrogen-containing crosslinking agent is 0.5wt%; and the Pt content in the platinum catalyst is 14000ppm.

[0062] Its preparation method includes the following steps: S1. Place the silica powder and fumed silica in a vacuum oven and dry at 115℃ and -0.08MPa for 30 min. S2. Add vinyl polydimethylsiloxane to the kneader, maintain 10°C, add the dry powder in 3 batches with an interval of 2 minutes between each batch, knead at 8 rpm for a total time of 18 minutes; evacuate to -0.09 MPa and continue kneading for 12 minutes. S3. Cool to 18°C, add crosslinking agent, catalyst and inhibitor in sequence, degas under vacuum at -0.09MPa for 10 minutes, and flatten the 2mm sheet with a glass plate.

[0063] Example 7 This embodiment provides a primary molding silicone rubber, which, by weight percentage, comprises the following raw materials: 45wt% vinyl polydimethylsiloxane, 40wt% silica powder, 12wt% fumed silica, 10wt% hydrogen-containing crosslinking agent, 0.06wt% 3-methyl-1-butyn-3-ol and 0.8wt% platinum catalyst.

[0064] The viscosity of vinyl polydimethylsiloxane is 75000 mPa·s; the median particle size D50 of the silica powder is 20 μm, and the bulk density is 0.8 g / cm³. 3 Tap density 1.7 g / cm³ 3 The compression ratio is 2.13; the median particle size D50 of the fumed silica is 100 nm, and the loose packing density is 0.18 g / cm³. 3 Tap density 0.22 g / cm³ 3 The compression ratio is 1.22; the Si-H content of the hydrogen-containing crosslinking agent is 1.8 wt%; and the Pt content in the platinum catalyst is 16000 ppm.

[0065] Its preparation method includes the following steps: S1. Place the silica powder and fumed silica in a vacuum oven and dry at 128℃ and -0.08MPa for 30 min. S2. Add vinyl polydimethylsiloxane to the kneader, maintain 28°C, add the dry powder in 3 batches with an interval of 2 minutes between each batch, knead at a speed of 18 rpm, for a total time of 16 minutes; evacuate to -0.09 MPa and continue kneading for 19 minutes. S3. Cool to 18°C, add crosslinking agent, catalyst and inhibitor in sequence, degas under vacuum at -0.09MPa for 14 minutes, and flatten the 2mm sheet with a glass plate.

[0066] Example 8 This embodiment provides a primary molding silicone rubber, which, by weight percentage, comprises the following raw materials: 40wt% vinyl polydimethylsiloxane, 38wt% silica powder, 20wt% fumed silica, 15wt% hydrogen-containing crosslinking agent, 0.04wt% 3-methyl-1-butyn-3-ol and 2.0wt% platinum catalyst.

[0067] The viscosity of vinyl polydimethylsiloxane is 50,000 mPa·s; the median particle size D50 of the silica powder is 5 μm, and the bulk density is 0.65 g / cm³. 3 Tap density 1.35 g / cm³ 3 The compression ratio is 2.08; the median particle size (D50) of the fumed silica is 15 nm, and the loose packing density is 0.09 g / cm³. 3 Tap density 0.15 g / cm³ 3 The compression ratio is 1.67; the Si-H content of the hydrogen-containing crosslinking agent is 0.9wt%; and the Pt content in the platinum catalyst is 11000ppm.

[0068] Its preparation method includes the following steps: S1. Place the silica powder and fumed silica in a vacuum oven and dry at 128℃ and -0.08MPa for 30 min. S2. Add vinyl polydimethylsiloxane to the kneader, maintain 28°C, add the dry powder in 3 batches with an interval of 2 minutes between each batch, knead at a speed of 18 rpm, for a total time of 16 minutes; evacuate to -0.09 MPa and continue kneading for 19 minutes. S3. Cool to 18°C, add crosslinking agent, catalyst and inhibitor in sequence, degas under vacuum at -0.09MPa for 14 minutes, and flatten the 2mm sheet with a glass plate.

[0069] Comparative Example 1 This comparative example provides a primary impression silicone rubber, with raw materials and preparation methods basically the same as in Example 2, the only difference being: the median particle size D50 of the silica powder is 6 μm and the loose packing density is 0.25 g / cm³. 3 Tap density 0.9 g / cm³ 3 And a compression ratio of 3.6.

[0070] Comparative Example 2 This comparative example provides a primary impression silicone rubber, with raw materials and preparation methods basically the same as in Example 3, the only difference being: the viscosity of vinyl polydimethylsiloxane is 65000 mPa·s; the median particle size D50 of fumed silica is 20 μm, and the bulk density is 0.25 g / cm³. 3 Tap density 0.3 g / cm³ 3 And a compression ratio of 1.2.

[0071] Comparative Example 3 This comparative example provides a primary impression silicone rubber, with raw materials and preparation methods basically the same as in Example 2, the only difference being: the median particle size D50 of the silica powder is 6 μm and the loose packing density is 0.15 g / cm³. 3 Tap density 0.45 g / cm³ 3 And a compression ratio of 3.0.

[0072] Comparative Example 4 This comparative example provides a primary impression silicone rubber, with raw materials and preparation methods basically the same as in Example 2, the only difference being: the median particle size D50 of the silica powder is 6 μm and the loose packing density is 0.95 g / cm³. 3 Tap density 2.0 g / cm³ 3 And a compression ratio of 2.11.

[0073] Test case The silicone rubber of Examples 1-8 and Comparative Examples 1-4 of the present invention were tested.

[0074] The testing methods are based on relevant national and international standards to ensure the scientific validity, accuracy, and repeatability of the test results. Specific guidelines are as follows: (1) Density test: Loose packing density: Use a loose packing density meter, selecting 100cm³. 3 Container, loose packing density = 100cm³ 3 Powder mass in container / 100cm 3 Volume.

[0075] Tap density: Use a tap density meter, select 70cm². 3 Container, tapped density = 70cm³ 3 Mass of powder / Volume of powder after compaction.

[0076] (2) Tensile strength and tear strength test Instrumentation: An electronic universal testing machine is used. The range of the testing machine should meet the requirements of the tensile strength and tear strength of the tested materials, and the accuracy should not be less than ±1%.

[0077] Specimen preparation: Dumbbell-shaped tensile specimens and right-angle tear specimens shall be prepared using standard molds in accordance with the requirements of GB / T528-2009 and GB / T529-2008. Specimen dimensions shall conform to the tolerances specified in the standards to ensure the accuracy of test results. During specimen preparation, any defects that may affect test results, such as air bubbles and impurities, shall be avoided.

[0078] Test conditions: The ambient temperature was controlled at (23±2)℃, and the relative humidity was controlled at (50±5)%. Before testing, the samples should be placed under standard environmental conditions for more than 24 hours to allow the materials to reach equilibrium. During testing, the tensile testing machine was set to a tensile speed of 500 mm / min, and the tear testing machine was set to a tear speed of 100 mm / min. These speed parameters meet the standard requirements and can ensure the stability and repeatability of the test results.

[0079] Testing Procedure: The prepared specimen is mounted on the fixture of the testing machine, ensuring it is secure and without skewing. The testing machine is started, and the force and displacement data of the specimen during the tensile and tearing processes are recorded. When the specimen breaks, the testing machine automatically stops, and the tensile and tear strength values ​​of the specimen are calculated using analysis software. At least five specimens are tested for each embodiment and comparative example, and the average value is taken as the final test result.

[0080] (3) Shore A hardness test Hardness testing was conducted in accordance with GB / T531.1-2008 "Determination of hardness of vulcanized rubber or thermoplastic rubber (Shore hardness tester method)".

[0081] Instrumentation: A Shore A hardness tester is used, with a measurement range of 0-100HA and an accuracy of ±1HA.

[0082] Sample preparation: Prepare a flat, uniformly thick silicone rubber sample. The sample surface should be smooth and free of obvious defects and impurities. The sample dimensions should meet the contact requirements of the hardness tester's measuring head, ensuring that the measuring head can be pressed vertically and stably onto the sample surface during measurement.

[0083] Test conditions: The ambient temperature is controlled at (23±2)℃ and the relative humidity is controlled at (50±5)%. Before the test, the hardness tester should be placed under standard environmental conditions for more than 30 minutes to ensure the stability of the instrument and the accuracy of the measurement results.

[0084] Test Procedure: Place the sample on a stable test platform, press the hardness tester head vertically onto the sample surface, and apply the specified test force (10N). Maintain the contact time between the measuring head and the sample surface for 15 seconds, and then read the reading on the hardness tester. Measure the hardness values ​​at at least 5 different locations for each sample, and take the average value as the hardness result for that sample.

[0085] (4) Surface roughness test Surface roughness was tested in accordance with GB / T10610-2009 "Evaluation of the arithmetic mean deviation of the profile of the surface structure profile method in the product geometric technical specification (GPS)".

[0086] Instrumentation: High-precision surface roughness measurement instruments such as optical profilometers or atomic force microscopes (AFM) are used. The measurement range of the optical profilometer should cover surface roughness values ​​of 0.01-10 μm, with an accuracy of not less than ±0.01 μm. The AFM has a wider measurement range and can measure surface roughness at the nanometer level, making it suitable for measuring high-precision surface roughness.

[0087] Sample preparation: Prepare thin, flat sheets of silicone rubber material with uniform thickness. The sample surface should be free of obvious scratches, stains, or other factors that may affect the measurement results. The sample dimensions should meet the requirements of the instrument's measurement platform to ensure stable placement of the sample during the measurement process.

[0088] Test conditions: The test environment should avoid direct sunlight and vibration interference. The temperature should be controlled at (23±2)℃ and the relative humidity at (50±5)%. Before the test, the instrument should be preheated and calibrated to ensure the stability and accuracy of the measurement system.

[0089] Testing Procedure: Place the sample on the instrument's measuring platform and adjust the instrument's measurement parameters, such as setting the sampling length to 2.5 mm. The evaluation length is determined based on the actual surface conditions of the sample. Start the instrument to scan and measure the sample surface. The instrument automatically calculates and outputs the surface roughness Ra value. Measure the surface roughness at least three different locations for each sample, and take the average value as the final result.

[0090] (5) Imprint accuracy test Impression accuracy was tested in accordance with ISO 4823 "Determination of accuracy of dental impression materials".

[0091] Instrumentation: A standard metal master mold and a reading microscope are used. The standard metal master mold should meet the dimensional accuracy requirements of ISO 4823, with a high surface finish and free from deformation and wear. The reading microscope should have a measurement accuracy of ±0.01 mm, enabling precise measurement of dimensional changes in the impression material after curing.

[0092] Sample preparation: After mixing the silicone rubber material evenly according to the specified ratio, pour it into a standard metal master mold, ensuring that the material fully fills all parts of the master mold and avoiding air bubbles and unfilled areas. During the curing process, strictly follow the material's curing conditions to ensure complete curing.

[0093] Test conditions: The ambient temperature is controlled at (23±2)℃ and the relative humidity is controlled at (50±5)%. Before the test, the standard metal master mold and the reading microscope should be preheated for more than 30 minutes under standard environmental conditions to ensure the accuracy of the test results.

[0094] Testing process: After the silicone rubber material has cured, the impression is removed from the standard metal master mold. The size of the impression is measured at multiple locations using a reading microscope and compared with the size of the standard metal master mold. The size of the scale line of the impression is then read.

[0095] (6) Characterization of powder dispersion By using high-resolution SEM (scanning electron microscope) images and randomly selecting multiple fields of view for imaging, the dispersion uniformity of powder can be evaluated intuitively and accurately, providing an important reference for optimizing material properties.

[0096] Powder dispersion test results classification: No reunion: such as Figure 1 As shown, the two types of powders are completely dispersed without agglomeration, and the dispersion spacing is arranged accordingly. Very few reunions: such as Figure 2 As shown, the powder is well dispersed, but there are a very small amount of agglomeration. Trace aggregates: such as Figure 3 As shown, the powder dispersion exhibited slight agglomeration; Small gatherings: such as Figure 4 As shown, a small amount of agglomeration occurred in the powder dispersion.

[0097] The test results are shown in Table 1.

[0098] Table 1. Performance test results of silicone rubber for initial impression molding

[0099] The test results show that Examples 2 and 3 exhibit the best overall performance in terms of impression accuracy, Shore A hardness, tensile strength, tear strength, surface roughness Ra, and processing time. They not only possess the highest Shore A hardness but also demonstrate high tensile and tear strength. Furthermore, the surface roughness of these two samples is very well controlled, and no agglomeration was observed under electron microscopy, indicating good internal material uniformity. Simultaneously, their processing time remains ≤2 hours, which helps improve production efficiency without sacrificing product quality.

[0100] Compared to Comparative Example 1 and Example 2, the impression accuracy decreased to 50 μm, Shore A hardness and tensile strength both decreased, tear strength remained relatively unchanged, but roughness Ra significantly increased to 0.54 mm. This is because the low bulk density and high compression ratio of the surface silica powder are detrimental to the uniform dispersion of the powder in the silicone rubber matrix, leading to a significant increase in surface roughness and affecting impression accuracy and mechanical properties.

[0101] Compared to Comparative Example 2 and Example 3, the particle size of fumed silica increased to 20 μm, and the loose packing density increased to 0.25 g / cm³. 3 The tap density is 0.3 g / cm³. 3 The compression ratio decreased to 1.2. As a result, the molding accuracy decreased significantly to 75 μm, the processing time increased to 120 min, and the surface roughness Ra also increased to 0.56 mm. This indicates that the nanoscale particle size of fumed silica has a decisive influence on its dispersibility, reinforcing effect, and surface finish in the system, and that micron-sized silica particles cannot effectively improve the molding accuracy and surface quality of silicone rubber.

[0102] Compared to Comparative Example 3 and Example 2, the loose packing density of the silicon micropowder was further reduced to 0.15 g / cm³. 3 The tap density is 0.45 g / cm³. 3 The compression ratio was 3.0. Although the mold accuracy was still poor, the tensile strength improved slightly, the surface roughness Ra increased significantly to 0.74 mm, and the processing time was extended to 130 min. This indicates that excessively low bulk density exacerbates the agglomeration tendency of powder during kneading, affecting processing efficiency and product uniformity, leading to a decline in overall performance.

[0103] Compared to Comparative Example 4 and Example 2, the loose packing density of the silicon micropowder increased to 0.95 g / cm³. 3 The tap density is 2.0 g / cm³. 3 The compression ratio decreased to 2.11. The molding accuracy remained poor, with both Shore A hardness and tensile strength decreasing, and the surface roughness Ra being high. This indicates that excessively high bulk density may lead to uneven dispersion of the powder in the matrix, thus reducing mechanical properties and surface quality, and affecting the final molding accuracy.

[0104] In summary, by using inorganic fillers with different loose packing densities, tapped densities, and compression ratios in combination, and ensuring a suitable ratio of the three, the filler particles are tightly packed, reducing internal porosity of the material. This reduces stirring resistance during processing, significantly improving processing efficiency, enhancing powder dispersion, and ensuring good processing at room temperature.

[0105] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A uniformly dispersed primary molding silicone rubber, characterized in that, The initial impression silicone rubber comprises the following components by weight percentage: 30-80 wt% vinyl polydimethylsiloxane, 11-80 wt% inorganic filler, 1-20 wt% hydrogen-containing crosslinking agent, 0-0.5 wt% inhibitor, and 0.01-5 wt% catalyst; The inorganic filler includes silica powder and fumed silica powder, wherein the loose packing density of the silica powder is 0.3-1 g / cm³. 3 Tap density: 0.9-1.8 g / cm³ 3 The compression ratio is 1.5-2.6; the loose packing density of the fumed silica is 0.02-0.2 g / cm³. 3 Tap density: 0.05-0.23 g / cm³ 3 The compression ratio is 1.4-2.

2.

2. The uniformly dispersed primary molding silicone rubber according to claim 1, characterized in that, The median particle size D50 of the silicon micro powder is 4-20 μm, and the content is 10-50 wt%; the median particle size D50 of the fumed silica powder is 1-100 nm, and the content is 1-30 wt%.

3. The uniformly dispersed primary molding silicone rubber according to claim 2, characterized in that, The median particle size D50 of the silicon micropowder is 5-15 μm; the median particle size D50 of the fumed silica powder is 1-30 nm.

4. A uniformly dispersed primary molding silicone rubber according to any one of claims 1-3, characterized in that, The initial impression silicone rubber comprises the following components by weight percentage: 40-70 wt% vinyl polydimethylsiloxane, 20-40 wt% silica powder, 5-20 wt% fumed silica powder, 3-15 wt% hydrogen-containing crosslinking agent, 0-0.5 wt% inhibitor, and 0.02-2 wt% catalyst.

5. The uniformly dispersed primary molding silicone rubber according to claim 1, characterized in that, The viscosity range of the vinyl polydimethylsiloxane is 10,000-100,000 mPa·s; the Si-H content in the hydrogen-containing crosslinking agent is 0.3-2.2 wt%; the inhibitor is at least one of alkynyl alcohols or maleic esters; the catalyst is a platinum catalyst, and the Pt content in the platinum catalyst is 1,000-20,000 ppm.

6. The uniformly dispersed primary molding silicone rubber according to claim 5, characterized in that, The viscosity of the vinyl polydimethylsiloxane is 30,000-80,000 mPa·s; the Pt content in the platinum catalyst is 10,000-20,000 ppm.

7. A method for preparing a uniformly dispersed primary impression silicone rubber as described in any one of claims 1-6, characterized in that, Includes the following steps: Silicon micropowder and fumed silica are vacuum dried to obtain a dry powder; the dry powder is added to vinyl polydimethylsiloxane for the first kneading; then vacuum treatment is performed for the second kneading; after kneading, the mixture is cooled, and then a crosslinking agent, catalyst, and inhibitor are added in sequence, followed by vacuum degassing to obtain the initial impression silicone rubber.

8. The method for preparing a uniformly dispersed primary impression silicone rubber according to claim 7, characterized in that, The vacuum drying temperature is 110℃-130℃, the vacuum degree is -0.06 to -0.08 MPa, and the drying time is 20-30 min.

9. The method for preparing a uniformly dispersed primary impression silicone rubber according to claim 7, characterized in that, The first kneading is performed at a speed of 1-30 rpm, a temperature of 10℃-30℃, and a kneading time of 10-20 min; the second kneading is performed at a vacuum of -0.09 to -0.1 MPa, a speed of 1-30 rpm, and a kneading time of 10-20 min.

10. The method for preparing a uniformly dispersed primary impression silicone rubber according to claim 7, characterized in that, The cooling temperature is ≤25℃; the vacuum degree of the vacuum degassing is -0.09 to -0.1 MPa, the temperature is 10℃ to 30℃, and the time is 10 to 15 min.